2018
DOI: 10.1016/j.jconrel.2018.04.026
|View full text |Cite
|
Sign up to set email alerts
|

Multi-modal characterization of vasculature and nanoparticle accumulation in five tumor xenograft models

Abstract: Preclinical research has demonstrated that nanoparticles and macromolecules can accumulate in solid tumors due to the enhanced permeability and retention effect. However, drug loaded nanoparticles often fail to show increased efficacy in clinical trials. A better understanding of how tumor heterogeneity affects nanoparticle accumulation could help elucidate this discrepancy and help in patient selection for nanomedicine therapy. Here we studied five human tumor models with varying morphology and evaluated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
45
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 51 publications
5
45
1
Order By: Relevance
“…Despite sufficient vascularization in the periphery, UPSN‐FITC uptake was severely retarded in MDA‐MB 231, when compared to 4T1 (almost five times lower; Figure A). This is in sharp contrast to previously reported observations involving larger (100–200 nm) or ultrasmall small (<6 nm) NPs, where MVD was demonstrated to play a central role in tumor uptake of NPs . These observations indicated that superficial parameters were insufficient to explain the intra‐tumoral kinetics of UPSNs, necessitating a closer look at the differences in tissue architectures of the two models.…”
Section: Resultscontrasting
confidence: 94%
See 1 more Smart Citation
“…Despite sufficient vascularization in the periphery, UPSN‐FITC uptake was severely retarded in MDA‐MB 231, when compared to 4T1 (almost five times lower; Figure A). This is in sharp contrast to previously reported observations involving larger (100–200 nm) or ultrasmall small (<6 nm) NPs, where MVD was demonstrated to play a central role in tumor uptake of NPs . These observations indicated that superficial parameters were insufficient to explain the intra‐tumoral kinetics of UPSNs, necessitating a closer look at the differences in tissue architectures of the two models.…”
Section: Resultscontrasting
confidence: 94%
“…However, blood vessels in the xenografts demonstrated significantly attenuated microstructure, with smaller diameters, mean areas, and perimeter measurements, when compared to faster growing syngeneic 4T1 tumors (Figure D–F). Interior of MDA‐MB 231 tumors demonstrated largely avascular, necrotic areas, with chaotic cellular islands, in accordance with the clinical observations in patients with aggressive tumors …”
Section: Resultssupporting
confidence: 89%
“…As an alternative to companion nanodiagnostics and nanotheranostics, clinically established (but intuitively significantly less specific) 'standard' imaging protocols could be considered to predict the accumulation and efficacy of passively targeted cancer nanomedicines, such as dynamic contrast-enhanced MRI 39 , CT 40 and ultrasound 41 . Furthermore, future analyses should set out to evaluate if histopathological assessment of tumour biopsies can help to stratify responders from non-responders.…”
Section: Imaging Biomarkersmentioning
confidence: 99%
“…The interesting study by Sulheim and colleagues is another example of multimodal imaging: 33 the authors investigated the organization and density of functional blood vessels that newly developed in a tumour tissue by intense angiogenesis. Actually, angiogenesis is crucial to understand how tumour heterogeneity affects the uptake and accumulation of therapeutic agents (among which NPs in nanomedical therapy).…”
Section: Imaging Techniques Applied To In Vivo Modelsmentioning
confidence: 99%